Visualising Inclusive School - Singh, Astha; Bajpai, Amita (Voices of Teachers and Teacher Educators, 2021)
The purpose of this study is to reflect how inclusion can be made possible in schools. In this paper, the researcher has carried out a qualitative review of previous studies to know what strategies can be used for inclusive schools. The researcher has categorised the strategies into two types: general strategies and specific strategies. General strategies include location of classroom, classroom environment, sitting arrangement in the classroom, support for physical and mental well-being, Teacher Education and regular training and specialised staff. Specific strategies include teaching strategies, IEP of children with special needs, teaching methods, curriculum and assessment, reinforcement, adaptation, accommodation and modification, assistive technologies, and life skills.